Repeated Use of Prescription Drugs in Pediatrics: Comprehensive Overview Based on German Claims Data - Scholle, Oliver; Neubert, Antje; Riedel, Oliver; Toni, Irmgard; Haug, Ulrike (Frontiers in Pharmacology, 2021)
Background: Investigating drug utilization in large and unselected samples of children and adolescents is an important component of public health monitoring. Most existing studies in this field focused on any drug use (i.e., ≥1 prescription of a certain drug) although chronic drug use may be more relevant. This study aimed to provide a comprehensive overview of prevalence and types of prescription drugs used repeatedly in children and adolescents in Germany in 2016. Methods: We used the German Pharmacoepidemiological Research Database (GePaRD)—a claims database covering ~20% of the German population. We included children and adolescents aged 0–17 years and assessed repeated use of prescription drugs (≥3 prescriptions in 2016) on two levels: therapeutic subgroups (ATC 2nd level) and chemical substances (ATC 5th level). Analyses were stratified by sex and age groups (<2, 2–5, 6–12, and 13–17 years). Results: Overall, 2.5 million children and adolescents were included. In the age groups below 13 years, the prevalence rates of repeated use of prescription drugs (ATC 2nd level) were higher in boys than in girls (113–152 vs. 83–130 per 1,000 person-years), whereas in the age group 13–17 years, they were twice as high in girls than in boys (236 vs. 118 per 1,000 person-years). In boys and girls aged below six years, systemic antibiotics, topical ocular antibiotics, and drugs for constipation were among the most common drugs used repeatedly. For higher ages, methylphenidate, levothyroxine, and combined hormonal contraceptives, were among the most common drugs used repeatedly. Conclusions: Overall, about one in ten children in Germany repeatedly used prescription drugs. This proportion as well as the type of drugs used repeatedly markedly varied by sex and age. For certain drugs, our findings raise concerns regarding appropriateness of prescribing that should be addressed in future studies.